EKSISTENSI TARI RADDAT KOKO DI DESA SEKUDUK KECAMATAN SEJANGKUNG KABUPATEN SAMBAS - Alfiya Nur Wisthania; Ismunandar Ismunandar; Imma Fretisari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThis study aims to describe the Existence of Raddat Koko Dance. The problem of this research is related to the development of Raddat Koko Dance from the ginning of it creation until now it can survive today and describes the factors that influence the development of Raddat Koko Dance. Descriptive method with qualitative research form and using historical approach by carrying out several steps, namely heuristics, linkages, interpretation, and historiography. Sources of data obtained by observation, interviews, and documentation. The data validity testing technique uses extension of observation, source triangulation and techniques. Raddat Koko Dance is a traditional dance originating from the Sekuduk Village of Sambas Regency. At first this dance was used to trick the Dutch invaders, so that peple who were practicing the martal arts movements were not suspected. From 1928 to 2019 the exixtence of Raddat Koko Dance still existed among the people. Usually this dance is welcoming ceremony, wedding, and Independence day celebrations. Keywords: The existence, Raddat Koko Dance